Time Domain Nuclear Magnetic Resonance (TD-NMR) to evaluate the effect of potato cell membrane electroporation. (October 2020) - Menegazzo, Ileana; Mammi, Stefano; Sgarbossa, Paolo; Bartolozzi, Alessandra; Mozzon, Mirto; Bertani, Roberta; Forzan, Michele; Sundararajan, Raji; Sieni, Elisabetta
Abstract: Time Domain-Nuclear Magnetic Resonance (TD-NMR) was used here for the first time to analyze potato specimens cut from tubers before and after electroporation. The proton transverse relaxation time, T2, was used to identify the modifications that occur at the cell level involving water molecules mobility in potato tubers after the electroporation treatment. Since electroporation modifies the tissue conductivity, the samples were also analyzed in terms of conductivity, water content, and microscopic morphology of the tissue. Comparison analyses were performed on dried potato (zero water content) and water-potato starch mixtures with different water contents. All the data confirm that the effect of the electroporation process can be identified with a variation of the position of the peaks in T2 distribution, associated to sub-cellular modifications. Highlights: Effect of electroporation on potato tissue quickly identified by TD-NMR T2 is very sensitive to water content changes due to age, position in the tuber, etc. Reduction of vacuole size evidenced by reduction of main T2 value and microspcopy TD-NMR to monitor water compartmentation in cells after electroporation